Editorial. Issue 1 (1st March 2021) - Welch, Penny; Wright, Susan
Abstract : In this issue of Learning and Teaching: The International Journal of Higher Education in the Social Sciences, authors from a range of academic disciplines – music therapy, political geography, social policy, international communications and law – explore some contemporary concerns in higher education.